2016
DOI: 10.1007/s10863-015-9642-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atp-dependent potassium uptake on mitochondrial functions under acute hypoxia

Abstract: The opening of mitochondrial K(+) АТР-channel (mtK(+) АТР-channel) is supposed to be important in the modulation of mitochondrial functions under hypoxia, but the underlying mechanisms have not been clarified yet. The aim of this work was to study the effect of acute hypoxia on mtK(+) АТР-channel activity and to estimate the contribution of the channel in the modulation of mitochondrial functions. MtK(+) АТР-channel activity was assessed polarographically from the rate of State 4 respiration and by potentiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 39 publications
4
16
0
Order By: Relevance
“…Worth mention, that main limitation of our study was the use of indirect methods to assess mK ATP -channel activity and inability of molecular identification of ATPsensitive K + transport sensitive to diazoxide in the absence of MgATP. However, an estimate of native mK ATP -channel activity (~40 nmol K + ·min − 1 ·mg − 1 ) using respiration and proton transport assays well agreed with the assessment of mK ATP -channel activity with K + -selective electrode (45.0 ± 5.0 nmol K + ·min − 1 ·mg − 1 ) by monitoring ATP-sensitive potassium efflux from deenergized mitochondria [26]. Also, sequential blockage of K + transport by Mg 2+ and ATP proved the activation of native mK ATP -channel by diazoxide.…”
Section: Discussionsupporting
confidence: 58%
“…Worth mention, that main limitation of our study was the use of indirect methods to assess mK ATP -channel activity and inability of molecular identification of ATPsensitive K + transport sensitive to diazoxide in the absence of MgATP. However, an estimate of native mK ATP -channel activity (~40 nmol K + ·min − 1 ·mg − 1 ) using respiration and proton transport assays well agreed with the assessment of mK ATP -channel activity with K + -selective electrode (45.0 ± 5.0 nmol K + ·min − 1 ·mg − 1 ) by monitoring ATP-sensitive potassium efflux from deenergized mitochondria [26]. Also, sequential blockage of K + transport by Mg 2+ and ATP proved the activation of native mK ATP -channel by diazoxide.…”
Section: Discussionsupporting
confidence: 58%
“…The inhibition of the pore activity following mKATP channels opening was shown to prevent the development of cellular apoptosis and necrosis under pathophysiological conditions [1,2,11]. Meanwhile, several published data, including the results of our work have shown that oxidative phosphorylation system is another important target of the pharmacological modulators of mKATP channels [12]. However, physiological meaning of the impact of mKATP channels opening on mitochondrial ATP synthesis is not quite well understood.…”
Section: Introductionmentioning
confidence: 73%
“…In our previous work we also tried to assess physiological relevance of the effect of mKATP channels opening on the oxidative phosphorylation by studying the impact of short-term acute hypoxia on the physical endurance of the animals subject to compulsory swimming with a load. By our observations, increase of mKATP channel activity after the short-term acute hypobaric hypoxia resulted in the improvement of the rats' endurance to physical stress, which prompted further extension of our research [12]. So, the aim of this work was to find the role of mKATP channel in the regulation of energy metabolism in vivo by examining the correlation between animals' endurance to exercise training and the endogenous mKATP channel activity.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Here and in [15] have found that the increase of conductivity of mitochondrial potassium channels of the rat liver and ATP-dependent K + inflow in acute hypoxia is an important chain of regulation of energy metabolism. Flocalin (activator of K ATP channels) modulates oxidative phosphorylation system of mitochondria (disrupted by 2,4-dinitrophenol) toward the side of ATP synthesis.…”
Section: T a B L E 1 The Changes Of Fibrinolytic Activity Of Plasma mentioning
confidence: 89%